The Sumo deadlift - Stewart, M. P.; Davies, T. B.; Godeassi, D. P. (Journal of Australian Strength and Conditioning, 2016)
The sumo deadlift is an exercise becoming increasingly popular in the strength and conditioning environment, both for improving physical performance and as a potential rehabilitation tool. Its uses for performance and rehabilitation are primarily due to the high level of musculature recruited to perform the movement and the decreased shearing forces placed on the spine. This article provides a detailed outline of the sumo deadlift, optimal technique, variations, its role in athletic performance and rehabilitation, and the prescription of this exercise.